Dynamical features of Venus ionosphere from comparative study of theoretical and in-situ measured electron density profiles - Upadhyay H.O.; Singh R.N. (My University, 2025)
A modeling of neutral density of Venusian gases for different solar activity and solar zenith angles has been made. Taking appropriate EUV solar flux data and selecting appropriate ionization and absorption cross-sections. The electron-ion pair production rates have been computed. Considering various reactions and their appropriate reaction rates the steady state ion density and electron density profiles have been computed in the altitude range of 100-800 Km. It is shown that the steady state ion densities and electron density below 250 Km. compare well with the theoretical results reported by various other workers and the in situ measurements by electron temperature probe (OETP) aboard Pioneer Venus Orbiter (PVO). However, the computed results above 250 Km. are shown to be considerably large. Using appropriate transport processes and matching the theoretical and in situ measured electron density profiles above 250 Km. the dynamical features of Venus ionosphere has been studied. The results thus obtained have been compared with other reported dynamical results. © 1989.